Human Papillomavirus (HPV) Genotypes in Condylomas, Intraepithelial Neoplasia, and Invasive Carcinoma of the Penis Using Laser Capture Microdissection (LCM)-PCR: A Study of 191 Lesions in 43 Patients. (June 2017) - Fernández-Nestosa, María J.; Guimerà, Nuria; Sanchez, Diego F.; Cañete-Portillo, Sofía; Velazquez, Elsa F.; Jenkins, David; Quint, Wim; Cubilla, Antonio L.
Abstract : Laser capture microdissection-polymerase chain reaction (LCM-PCR) supported by p16 INK4a was used for the first time to demonstrate human papillomavirus (HPV) DNA in histologically specific penile lesions, which were as follows: squamous hyperplasia (12 lesions, 10 patients), flat lesions (12 lesions, 5 patients), condylomas (26 lesions, 7 patients), penile intraepithelial neoplasia (PeIN) (115 lesions, 43 patients), and invasive squamous cell carcinomas (26 lesions, 26 patients). HPV was detected by whole-tissue section and LCM-PCR. LCM proved to be more precise than whole-tissue section in assigning individual genotypes to specific lesions. HPV was negative or very infrequent in squamous hyperplasia, differentiated PeIN, and low-grade keratinizing variants of carcinomas. HPV was strongly associated with condylomas, warty/basaloid PeIN, adjacent flat lesions, and warty/basaloid carcinomas. A single HPV genotype was found in each lesion. Some condylomas and flat lesions, especially those with atypia, were preferentially associated with high-risk HPV. Unlike invasive carcinoma, in which few genotypes of HPV were involved, there were 18 HPV genotypes in PeIN, usually HPV 16 in basaloid PeIN but marked HPV heterogeneity in warty PeIN (11 different genotypes). Variable and multiple HPV genotypes were found in multicentric PeIN, whereas unicentric PeIN was usually related to a single genotype. There was a correspondence among HPV genotypes in invasive and associated PeIN. p16 INK4a was positive in the majority of HPV-positive lesions except condylomas containing LR-HPV. p16 INK4a was usually negative in squamous hyperplasia, differentiated PeIN, and low-grade keratinizing variants of squamous cell carcinomas. In summary, we demonstrated that LCM-PCR was a superior research technique for investigating HPV genotypes in intraepithelial lesions. A significant finding was the heterogeneity of HPV genotypes in PeIN and the differential association of HPV genotypes with subtypes of PeIN. The presence of atypia and high-risk HPV in condylomas and adjacent flat lesions suggests a precursor role, and the correspondence of HPV genotypes in invasive carcinomas and associated PeIN indicates a causal relation. Data presented support the bimodal hypothesis of penile cancer carcinogenesis in HPV-driven and non-HPV-driven carcinomas and justify the current WHO pathologic classification of PeIN in special subtypes.